1991
DOI: 10.1099/00221287-137-4-859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron deprivation on surface composition and virulence determinants of Candida albicans

Abstract: Six strains of Candida albicans were grown in defined medium which had been deferrated by ion-exchange chromatography and then supplemented with FeCl, to give iron concentrations ranging from 0.026 p~ to 0.8 pM. Growth in 0-026 pM-iron (measured as increase in biomass) was reduced by 2659% as compared with that in excess (0.8 p~) iron. With five of the strains, adhesion to buccal epithelial cells was maximal after growth in 0.2-0-4pM-iron, but strain GDH 2023 adhered best when grown in 0 . 0 2 6~~-i r o n .Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Lan et al (18) reported that genes related to the TCA pathway were more highly expressed under the highiron condition; accordingly, our results would point to conditions with limited iron availability. Furthermore, iron depletion is known to alter the cell surface composition and hydrophobicity of C. albicans (31,41,42), and we found four genes encoding GPI-anchored proteins to be upregulated in response to MAb C7. In particular was RBT5, a protein from a family of pathogenesis-related heme-binding proteins (44) which is highly upregulated under low-iron conditions (16).…”
Section: Discussionmentioning
confidence: 88%
“…Lan et al (18) reported that genes related to the TCA pathway were more highly expressed under the highiron condition; accordingly, our results would point to conditions with limited iron availability. Furthermore, iron depletion is known to alter the cell surface composition and hydrophobicity of C. albicans (31,41,42), and we found four genes encoding GPI-anchored proteins to be upregulated in response to MAb C7. In particular was RBT5, a protein from a family of pathogenesis-related heme-binding proteins (44) which is highly upregulated under low-iron conditions (16).…”
Section: Discussionmentioning
confidence: 88%
“…The production of pseudohyphae by strain BWP17ctr1D : : URA3/ctr1D : : ARG4 in low-copper medium may result from the cell responding to copper-starved conditions. However, it has previously been observed that low-iron conditions affect hyphal growth in C. albicans (Sweet & Douglas, 1991) and so the lack of copper transport affecting iron uptake due to inactive CaFet3p activity may also be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CuRE-like elements in the promoter of CaCTR1 may facilitate tight control of copper uptake by a Mac1p-like transactivator, leading to copper homeostasis. Iron availability has been shown to affect C. albicans growth, hyphal production, adherence to host cells and the ability to set up an infection in mice (Sweet & Douglas, 1991;Valenti et al, 1986;Moors et al, 1992;Fratti et al, 1998;Eck et al, 1999;Ramanan & Wang, 2000). In S. cerevisiae the dependence of iron acquisiton on the uptake and delivery of copper to Fet3p is well documented and evidence suggests that a similar system operates in C. albicans (Morrissey et al, 1996;Eck et al, 1999;Hamacott et al, 2000;Ramanan & Wang, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other microbial pathogens, virulence of C. albicans is likely to be multifactorial ; characteristics such as proteinase secretion, adherence to host cells and hyphal production have all been implicated in virulence (Hube et al, 1997 ;Gale et al, 1998). Moreover, hyphal production and adherence have both been shown to be altered by growth in low-iron conditions (Sweet & Douglas, 1991a). It is probable, therefore, that iron acquisition plays a key role in the pathogenesis of C. albicans disease in ways similar to those proposed for many The EMBL accession number for the sequence reported in this paper is AJ387722.…”
Section: Introductionmentioning
confidence: 99%